Powwow - Ellis, Clyde, 1958-; Lassiter, Luke E.; Dunham, Gary H. (University of Nebraska Press, 2005)
This anthology examines the origins, meanings, and enduring power of the powwow. Held on and off reservations, in rural and urban settings, powwows are an important vehicle for Native peoples to gather regularly. Although sometimes a paradoxical combination of both tribal and intertribal identities, they are a medium by which many groups maintain important practices.